2020
DOI: 10.1136/jmedgenet-2019-106671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and genetic variations of LMNA-related muscular dystrophies in a large cohort of Chinese patients

Abstract: BackgroundLMNA-related muscular dystrophy is caused by mutations in LMNA gene. We aimed to identify genetic variations and clinical features in a large cohort of Chinese patients with LMNA mutations in an attempt to establish genotype-phenotype correlation.MethodsThe clinical presentations of patients with LMNA-related muscular dystrophy were recorded using retrospective and prospective cohort study. LMNA mutation analysis was performed by Sanger sequencing or next-generation sequencing. Mosaicism was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 31 publications
(37 reference statements)
9
29
0
Order By: Relevance
“… 7 , 37 , 38 The most common variant our cohort, an Arg249Trp substitution, was primarily associated with congenital and early onset laminopathies and has not been associated with later-onset clinical subttypes (EDMD or LGMD1B) ( www.umd.be/LMNA/ , GB and RBY personal communication ). This finding is similar to the one reported by Fan et al 25 in a large series of Chinese patients with 12/41 of their patients with L-CMD patients carrying this substitution. Other in-frame variants in our cohort (p.Asn39Ser, p.Lys32del, Glu358Lys, p.Arg453Trp) were less exclusively associated with laminopathies showing congenital or early-onset presentations (only 83.3%, 70%, 63.3% and 0% of published carriers showing congenital/early onset laminopathy, respectively).…”
Section: Discussionsupporting
confidence: 92%
“… 7 , 37 , 38 The most common variant our cohort, an Arg249Trp substitution, was primarily associated with congenital and early onset laminopathies and has not been associated with later-onset clinical subttypes (EDMD or LGMD1B) ( www.umd.be/LMNA/ , GB and RBY personal communication ). This finding is similar to the one reported by Fan et al 25 in a large series of Chinese patients with 12/41 of their patients with L-CMD patients carrying this substitution. Other in-frame variants in our cohort (p.Asn39Ser, p.Lys32del, Glu358Lys, p.Arg453Trp) were less exclusively associated with laminopathies showing congenital or early-onset presentations (only 83.3%, 70%, 63.3% and 0% of published carriers showing congenital/early onset laminopathy, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The disease manifests as slowly progressive scapulahumeroperoneal muscle weakness with rigid spine or scoliosis, childhood-onset contractures of the elbow, posterior cervical and ankle joints, and normal or mildly delayed motor milestones with gait abnormality and difficulty in running and jumping, going up and down stairs, and standing up from squatting. [10][11][12][13] In short, individuals with L-CMD exhibit more severe clinical manifestations and experience more rapid progression and earlier onset than individuals with EDMD do; however, EDMD has a higher risk of cardiac involvement, such as cardiomyopathy, conduction defects, tachyarrhythmias, and even atrial standstill, than that of L-CMD. Moreover, patients with mutations which are at the exon-intron or intron-exon junctions of the LMNA gene always present with an EDMD or DCM phenotype because of the pre-mRNA splicing abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Heart is affected in all the three entities, with similar features, except for younger age at onset in L-CMD and EDMD2 than LGMD1B, which also has later presentation of muscle weakness [45,100]. A study involving mainly patients in pediatric age at the end of the follow-up period, showed that cardiac involvement is significantly more frequent in EDMD2 than L-CMD and LGMD1B [101]. Notably, as in desminopathy, cardiac presentation may precede or follow onset of muscle weakness.…”
Section: Clinical Aspects Of Skeletal Muscle Involvement In Laminopatmentioning
confidence: 94%